2008
DOI: 10.1038/ijo.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of an additive inhibitory feeding effect following PP and PYY3−36 administration

Abstract: Pancreatic polypeptide (PP) and peptide YY (PYY) are released by the gut in response to nutrients and inhibit food intake in rodents and humans. We hypothesized that PP and PYY 3À36 would inhibit feeding additively. Fasted male C57BL/6 mice were injected intraperitoneally with saline, PP, PYY 3À36 or PP þ PYY 3À36 (n ¼ 7-10). Food intake at 1 h was significantly inhibited by 6 nmol kg À1 PP and by 6 nmol kg À1 PYY 3-36 (Po0.05) but not significantly following 3 nmol kg À1 PP þ 3 nmol kg À1 PYY 3À36 . In a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…However, studies performed on lean human volunteers do not always support this. Neary et al (30) reported that pancreatic polypeptide, a Y4 receptor agonist, and PYY 3–36 , a selective Y2 receptor agonist, did not reduce food intake when infused together. Others have found that, although cholecystokinin and glucagon-like peptide 1 (GLP-1) synergistically reduced hunger sensations, the combination did not reduce energy intake to a greater extent than infusion of either hormone separately (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies performed on lean human volunteers do not always support this. Neary et al (30) reported that pancreatic polypeptide, a Y4 receptor agonist, and PYY 3–36 , a selective Y2 receptor agonist, did not reduce food intake when infused together. Others have found that, although cholecystokinin and glucagon-like peptide 1 (GLP-1) synergistically reduced hunger sensations, the combination did not reduce energy intake to a greater extent than infusion of either hormone separately (31).…”
Section: Discussionmentioning
confidence: 99%
“…Band adjustments occurred 2 days (mean, 49.4 h) prior to testing and were blinded to the subject and investigators. The mean time between paired tests was 4.5 days (range, [2][3][4][5][6][7][8][9][10][11][12][13][14], and no weight difference was found. Participants were asked to guess their band status after adjustment to assess blinding; 13 (76.5%) were undecided, three (17.5%) were correct and one was incorrect (6%).…”
Section: Methodsmentioning
confidence: 90%
“…Both have been associated with increased satiety in humans [3], and concentrations have been found to rise to a peak in direct proportion to the calorie content of a meal [1,2]. Administration of exogenous PP and PYY has both been shown to reduce food intake in rodents and humans, but their effects do not appear to be additive [4,5]. Some controversy exists regarding whether levels are lower or perhaps augmented in obesity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to the hypothesis that treatment with multiple gut hormones could be better tolerated, and more effective, than single hormone treatment. Support for this hypothesis is available from small-scale studies of acute food intake in rodents and humans [99,116], although not all combinations have proven effective [209,210]. However, if nausea occurs not simply as a result of excessive satiety but also as a specific, independent side effect, it might be avoided, and weight loss maximized, by co-administration of non-nauseating doses of several hormones.…”
Section: Discussionmentioning
confidence: 99%